Association between positive youth development and family functioning in the Chinese context: a four-wave longitudinal survey in mainland China - Li, Xiang; Tang, Yi-Ting; Shek, Daniel T. L. (Frontiers in Psychology, 2024)
There is a notable scarcity of research examining the developmental trajectories of positive youth development (PYD) attributes among Chinese preadolescents and adolescents and the predictive effect of family functioning on these trajectories over time. Using four waves of data, this longitudinal study investigated preadolescents and adolescents in China in January 2020 (T1), June 2020 (T2), June 2021 (T3), and June 2022 (T4). The study utilized the 90-item "Chinese Positive Youth Development Scale" and the 33-item "Chinese Family Assessment Instrument" to assess PYD and family functioning, respectively. The final matched sample comprised 2,652 Chinese students from grades 4 to 8, with an average age of 10.9 years (SD = 1.32; range 9-15) at the first wave of the survey, and with 51.1% male (n = 1,354). Using Latent Growth Curve Modeling (LGCM), the unconditional LGCM revealed that the PYD developmental trajectories of preadolescents and adolescents followed a quadratic U-shaped curve, characterized by an initial decline from T1 to T3, followed by a rebound from T3 to T4. Although the time-invariant covariate LGCM indicated no significant gender difference in the initial level of PYD, girls exhibited a slower decline rate and a faster growth rate in PYD over time than did boys. The parallel LGCM demonstrated that initial levels of family functioning significantly and positively predicted both the initial level and the rate of change in PYD over time. This study highlights the critical importance of considering the direct and sustained impact of family functioning within Chinese contexts on positive developmental outcomes among Chinese preadolescents and adolescents. This study also suggests that when designing and formulating specific programs or interventions, it is essential to consider gender differences in the development of competencies to ensure the optimal development of young individuals of different genders.